2015
DOI: 10.1002/hbm.22863
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic correlates of metabolic network activity in Parkinson's disease

Abstract: Parkinson's disease (PD) is associated with distinct metabolic covariance patterns that relate to the motor and cognitive manifestations of the disorder. It is not known, however, how the expression of these patterns relates to measurements of nigrostriatal dopaminergic activity from the same individuals. To explore these associations, we studied 106 PD subjects who underwent cerebral PET with both (18) F-fluorodeoxyglucose (FDG) and (18) F-fluoro-L-dopa (FDOPA). Expression values for the PD motor- and cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 39 publications
(132 reference statements)
6
70
1
1
Order By: Relevance
“…Although a trend was observed, PDRP and striatal DAT binding were not significantly correlated. Previous studies in PD have shown that PDRP expression shows only modest correlation to DAT binding 10, 28, 29. This may indicate a partly nondopaminergic genesis of the PDRP.…”
Section: Discussionmentioning
confidence: 80%
“…Although a trend was observed, PDRP and striatal DAT binding were not significantly correlated. Previous studies in PD have shown that PDRP expression shows only modest correlation to DAT binding 10, 28, 29. This may indicate a partly nondopaminergic genesis of the PDRP.…”
Section: Discussionmentioning
confidence: 80%
“…After anatomic registration and ratio-normalization, a common and straightforward approach to the analysis of 18 F-FDG PET images is the application of univariate models in the software package statistical parametric mapping (SPM; http://www.fil.ion.ucl.ac.uk/spm/). In such studies, regions of altered relative 18 F-FDG uptake in patients compared with controls are identified or correlations between 18 F-FDG uptake in certain regions and clinical metrics are determined.…”
Section: Analysis Of 18 F-fdg Pet Imagesmentioning
confidence: 99%
“…The components that best discriminate between controls and patients are identified as the relevant disease-related pattern. An important advantage of this approach is that once a pattern has been identified, the degree of its expression can be quantified in any 18 F-FDG PET scan. This expression score is reflected by a single numeric value that can be used to investigate relationships with clinical or physiologic metrics or to make predictions.…”
Section: Analysis Of 18 F-fdg Pet Imagesmentioning
confidence: 99%
See 2 more Smart Citations